SOSIALISASI PROGRAM SEKOLAH RAMAH ANAK GUNA MENDUKUNG KEBIJAKAN KOTA LAYAK ANAK DI KOTA BENGKULU - Ika Pasca Himawati; Heni Nopianti; Diyas Widiyarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Child-friendly schools, often abbreviated as SRA, is one of the programs included in the assessment of the Child-Friendly City policy in Bengkulu City. As the presence of a program, the child-friendly school program is a crucial aspect to be socialized to the community component. Especially those at the education unit level, namely schools. This is an effort so that the program can be implemented to create a safe and comfortable environment for children. The method in this community service activity is socialization through counselling and interactive discussion, and question and answer. The activity virtually with the target audience, including principals and teacher representatives at the SD, SMP, SMA/SMK levels throughout Bengkulu City. Socialization activities organized and supported by DP3APPKB Bengkulu City and Province as the leading sector and Provincial, Education Authorities in city and level Province, Bengkulu University Research and Community Service Institute and Level Child-Friendly School facilitators,. The socialization carried out covered several things, including those related to the Convention on the Rights of the Child, the Legal Basis for the implementation of the SRA program, as well as all aspects related to SRA such as the meaning, function, purpose and benefits of SRA when applied in education units. In addition, there is information related to the stages of SRA implementation to sharing sessions related to the description of SRA practices in schools. In this activity, the steps for forming the SRA include what is known as